A PSYCHOANALYSIS ON THE MAIN CHARACTER IN DUBLINERS BY JAMES JOYCE - Regita Gonibala; Ana Mariana (Universitas Muhammadiyah Gorontalo, 2022)
AbstractThis study aims to analysis the id, ego and superego of the main character in each short story. In conducting this research, researchers used a qualitative descriptive method. Researchers used documentation as a data collection technique. All the data needed related to this study were collected by taking several steps, namely the researcher chose 5 short stories by James Joyce, then the researcher collected literary references related to the psychological approach. Based on the results of data analysis, it can be concluded that from the five short stories by James Joyce that have been selected by the researcher, there are id, ego and super ego of each main character in each short story.Keywords: Short Story, Psychoanalysis, Dubliners.